2000
DOI: 10.1007/s002689910056
|View full text |Cite
|
Sign up to set email alerts
|

Radical Resection of Periampullary Tumors in the Elderly: Evaluation of Long‐term Results

Abstract: Increasingly, patients of advanced age are coming for evaluation of periampullary tumors. Although several studies have demonstrated the safety of resecting periampullary tumors in older patients, few long-term survival data have been reported. Between 1983 and 1992 various periampullary masses were resected in 70 patients over age 65 (range 65-87 years). Total pancreatectomy was performed in 11 patients, and 59 patients underwent pancreaticoduodenectomy. The mean duration of hospitalization was 17 +/- 15 days… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
68
2
2

Year Published

2001
2001
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(79 citation statements)
references
References 20 publications
7
68
2
2
Order By: Relevance
“…The reported median overall survival ranged from 14-38 months and 5-year survival rates ranged from 12-31% (15,17,27,39). In the present study, the median survival time of the two groups were 17 months in the old group and 23 months in the young group.…”
Section: Discussionmentioning
confidence: 40%
“…The reported median overall survival ranged from 14-38 months and 5-year survival rates ranged from 12-31% (15,17,27,39). In the present study, the median survival time of the two groups were 17 months in the old group and 23 months in the young group.…”
Section: Discussionmentioning
confidence: 40%
“…Although the elderly population has a higher prevalence of comorbidities, American Society of Anesthisiologists (ASA) scores and co-morbidities were evenly distributed between the two age groups [36,39,40,42,43]. Furthermore, patients with ASA grade IV were either excluded from pancreatic resection or were in the minority [24, 32-34, 38, 39].…”
Section: Pancreatic Resection For Pancreatic and Ampullary Cancermentioning
confidence: 99%
“…Some studies have shown that for resectable pancreatic carcinoma, pancreatic resections can be performed for the elderly with acceptable morbidity and mortality rates and possible long-term outcome [17,18,19,20,21,22,23,24,25]. However, in locally advanced pancreatic carcinoma treated with chemoradiotherapy, the tolerability, efficacy of treatment and long-term outcome have not been discussed extensively.…”
Section: Introductionmentioning
confidence: 99%